Parasitic infections encountered by a cytopathologist: An institutional experience - Pooja Jaiswal; Javed Iqbal; Nausheen S Khan; Pradeep Tandon; Mousumi Sharma; Megha Agarwal (Asian Journal of Medical Sciences, 2022)
Background: Parasitic infections are one of the leading causes of morbidity and mortality worldwide. Cytological examination can be of great help in providing economical, accurate, and fast diagnosis. Aims and Objectives: The aim of the study was to analyze the cytomorphological features of various parasites on fine needle aspirates and vaginal smears. Materials and Methods: This study was a retrospective study of 5.5 years during the time period from July 2015 to December 2020. The study included cases which were already diagnosed as having or suspicious of various parasitic infections on cytological examination. Results: There were total of 37 specimens comprising of 28 fine needle aspiration cytology (FNAC) smears and nine vaginal smears. The parasites on FNAC included 17 cases of cysticercus, eight cases of filariasis, two cases of hydatid disease, and one case of leishmaniasis. All the nine vaginal smears were interpreted as trichomonas vaginitis. Conclusion: Cytomorphological examination helps in early definitive diagnosis and exclusion of various parasitic infections. Diagnosis is important as most of these parasites are treatable and have several systemic ramifications.